Generalized Euler-Riesz difference sequence space with a paranormed fractional ordered ? - Tuz, Munevver; Bektas, Cigdem Asma (Zhejiang Univ Press, 2026)
In this study, we introduce the sequence space & ell;mu(p, Delta m) with a fractional order mu. Furthermore, we give some topological properties of this space. Also we introduce alpha-, beta-, and gamma-duals of & ell;mu(p, Delta m) and its some matrix mappings.
Keywords: Euler-Riesz sequence space; difference sequence space; paranorm; alpha-, beta-and gamma-duals; matrix transformations